Caracterização, classificação e aptidão agrícola de solos em projeto de assentamento na chapada do Apodi, RN - Costa, Joseane Dunga da (Universidade Federal Rural do Semi-Árido, 2018)
The use of land according to its suitability is the basic principle of soil and water conservation. Based on this, the general objective of this work was to characterize, classify and evaluate the agricultural aptitude of soils in the Chapada do Apodi, RN, indicating the limiting factors and potentialities, in order to seek agri-environmental planning. The research was carried out in the Terra de Esperança Settlement Project, located in the municipality of Governador Dix-Sept Rosado in Rio Grande do Norte, where ten sites were chosen to open the profiles of representative soils, such as: Native Forest Areas 1, 2 e 3 (NFA1 – P1, NFA2 – P7 e NFA3 – P9), Collective Area with Native Forest (CNF – P2), Agroecological area (AEA – P3), Cashew crop Area (CCA – P4), Collective Area with Pasture 1 e 2 (CAP1 – P5 e CAP2 – P6), Permanent preservation area (PPA – P8) e Cajaraneira (Spondia sp.) Orchard Area (COA – P10). A survey was made of the physical environment, covering the study area, including environmental factors such as soil, climate, relief, vegetation and hydrology. Ten soil profiles, morphological description, deformed and undisturbed samples for physical and structural analyzes and soil chemistry, geo - referenced pedological classification, as well as infiltration field tests and soil mechanical resistance to penetration were performed. The data of the attributes were expressed by the average of three replicates per horizon, and subjected to multivariate statistical analysis to detect the most sensitive attributes in the environments. The classes of soils found were: Cambissolo Háplico Carbonático vertissólico (P1 – NFA1), Cambissolo Háplico Carbonático típico (P2 – CNF and P3 – AEA), Cambissolo Háplico Ta Eutrófico típico (P6 – CAP2, P7 – NFA2 e P10 - COA), Cambissolo Háplico Ta Eutrófico vertissólico (P9 – NFA3), Argissolo Vermelho Distrófico latossólico (P4 – CCA), Chernossolo Rêndzico Órtico saprolítico (P5 – CAP1) and Neossolo Flúvico Ta Eutrófico típico (P8 – PPA). The Argissolo (P4 - CCA) was the only one to present acid character, aluminum saturation and low saturation by bases, dystrophic and low cation exchange capacity, forming horizons with chemical limitations, due to the latossolic character. The most sensitive attributes in the soil class distinction are related to the source material, which directly influenced the physical (silt and clay) and chemical (acidity, salinity, nutrient availability and clay fraction) physical characteristics of soils. The physical and structural attributes of Cambissolos Háplicos were generally preserved in relation to the current condition of the native forest, even under different uses and management of the soil, although the soils under use in the native forest areas 1, Conventional and Agroecological naturally denote fragility in aggregate stability and flocculation degree, due to the predominance of the sand fraction. The evaluation of agricultural aptitude revealed that the lands of the Terra da Esperança Settlement Project have a high agricultural potential, favored mainly by the good soil and relief conditions, differing only in the management level A (primitive) and the Cambissolo Háplico in the area of the P1 (NFA1), as regular. The main limitations are related to phosphorus fixation, water deficiency and impedance to mechanization in terms of effective soil depth. However, the replicates in the areas of P2 (CNF) and P10 (COA) were the ones that had the least limitations on their agricultural use (tillage). As there is also indication for less intensive activity, like natural pasturage for the Chernossolo Rêndzico (P5 – CAP1) and Cambissolo Háplico (P6 – CAP2); with the Neossolo Flúvico (P8) as an area for the preservation of flora and fauna, due to legislative restriction, being a permanent preservation area defined by INCRA
Keywords: Processos pedogenéticos; Calcário jandaíra; Potencial das terras; Planejamento agroambiental; Pedogenic processes; Jandaíra limestone; Land potential; Agro-environmental planning; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO